Dakwah Media Internet: Komparasi Situs Islam di Amerika dan Indonesia - Hatta Abdul Malik (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2016)
Goal of Propaganda of Islam through the Internet, one of which is to provide information about Islam to non-Muslims and Muslims. To the non-Muslims, Propaganda of Islam through the Internet is introducing the teachings of Islam. As for Muslim, Propaganda of Islam through the Internet is improving conversion and faith. This article tried to compare the Islamic website in America and Indonesia. Islam in American website contains more detail of Islamic teachings than Islam in Indonesian website. This is probably due to the majority of followers of Islam in Indonesia when compared to Islam in America.***Tujuan dakwah Islam melalui internet, salah satunya adalah memberikan informasi tentang Islam kepada non muslim dan muslim. Kepada non-muslim, dakwah melalui internet untuk mengenalkan ajaran Islam. Sedangkan bagi muslim dakwah melalui internet untuk meningkatkan keislaman dan keimanan. Artikel ini mencoba mengkomparasikan website Islam di Amerika dan website Islam di Indonesia. Website Islam di Amerika berisi lebih lengkap mengenai ajaran Islam dibandingkan website Islam di Indonesia. Hal ini barangkali disebabkan penganut Islam di Indonesia mayoritas jika dibandingkan dengan Islam di Amerika (minoritas).